Hyperspectral multi-indicator ripeness perception model for mechanized harvesting of “Yulu Xiang” pears - Na Ma; Jinyan Sun; Yingjun Li; Shijun Sun; Chenfei Li; Yile Sun; Zonglin Liu; Wendong Niu; Xiaoqin Xue; Haiyan Song (Computers and Electronics in Agriculture, 2026)

From dynamic scene understanding to stable feed delivery: A multi-sensor robotic system for autonomous precision feeding in intensive goat barns - Haoming Sun; Huaibo Zhou; Yu Pan; Lingyu Qiu; Zikang Chen; Yi Zhang; Xingjian Gu; Yingjun Xiong; Yanli Zhang; Yan Luo; Mingzhou Lu (Computers and Electronics in Agriculture, 2026)

Synergistic activation of CO2 and H2 by Ru-Oxygen vacancy pairs over porous CeO2 for efficient formic acid synthesis - Liujun Wang; Shufeng Lin; Junfeng Qian; Yingjun Wang; Zhe Wang; Zhonghua Sun; Zhihui Zhang; Bing Lu; Mingyang He; Zhenzhen Wang (Fuel, 2026)

Key three-material system in alkaline water electrolysis for hydrogen production: Systematic review and future outlook - Zhimeng Zhao; Hexu Sun; Jianhui Li; Zhanying Sun; Yingjun Guo (Fuel, 2026)

Endothelial AGO1 deficiency reduces breast cancer burden in mice - Xuejing Liu; Alonso Tapia; Dongqiang Yuan; Xiaofang Tang; Yingjun Luo; Naseeb Kaur Malhi; Muxi Chen; Kwan Ho Law; Mohamad Haidar; Skylar Giacobetti; Jiawei Sun; Anthony Park; et al. (Angiogenesis, 2026)
Endothelial cells (ECs) are crucial in cancer development and progression, partly by regulating tumor angiogenesis and immune modulation. As a key component of the RNA-induced silencing complex, Argonaute 1 (AGO1) regulates tumor biology, yet the specific function of AGO1 within ECs in the tumor microenvironment remains undefined. Here, we investigated the effects of endothelial-specific AGO1 knockout (EC-AGO1-KO) on tumor vascularization and immune regulation in a mouse syngeneic breast cancer model induced by E0771 cells. EC-AGO1-KO mice exhibited significantly reduced tumor burden compared to their wild-type (WT) littermates, accompanied by reduced vascularization and enhanced immune cell infiltration. Histological and single-cell RNA sequencing analyses revealed increased infiltration of CD8⁺ T cells and macrophages in EC-AGO1-KO tumors, indicative of an immunostimulatory microenvironment. In vitro, AGO1 knockdown in mouse ECs co-cultured with E0771 tumor cells led to higher levels of Cxcl10 and Vcam1 expression, suggesting a pro-inflammatory and leukocyte-recruiting effect. Together, these findings identify endothelial AGO1 as a key regulator of tumor vasculature and immune homeostasis in breast cancer, suggesting that targeting endothelial AGO1 may represent a novel therapeutic strategy to modulate tumor vasculature while enhancing anti-tumor immunity.

Oxygen stress drives overcompensation of carbon sources for enhanced polymer denitrification - Liping Huang; Longkang Feng; Yue Sun; Zhuo Li; Li Deng; Peng Zhang; Xiaohua Li; Dongdong Gao; Yingjun Wang; Shihuai Deng; Fei Shen; Dexin Fang (Water Research, 2026)

Discovery and screening of thermostable signature peptides for robust quantification of wheat allergens in processed foods - Yingjun Lu; Xiaojing Yu; He Li; Jingwen Sun; Yan Chen; Xiaomei Zhang; Xiaosha Wen; Dixian Luo; Hua Ji; Hongwei Zhang (Food Chemistry, 2026)

Quantitative Assessment of Inter-Borehole Competitive Interference on Effective Extraction Radius in Underground Coalbed Methane Extraction - Lin Wang; Shuhao Liang; Erlei Su; Xiangjun Chen; Lin Li; Yingjun Sun (Natural Resources Research, 2026)

Tracing coastal nonpoint sources of agricultural organic pollution based on soil sequestration and retention processes: A case study of the Yellow River Delta, China - Youxiao Wang; Zhaomin Zhang; Zhonghe Zhao; He Li; Yingjun Sun; Chong Huang; Banghua Zhang; Gaohuan Liu (Journal of Contaminant Hydrology, 2026)

Fatal infection of a novel canine/human reassortant H3N2 influenza A virus in the zoo-housed golden monkeys - Xia Wen; Rong Chen; Yingjun Lv; Jinzhu Geng; Jingjing Guo; Yaru Sun; Aohan Yang; Yuhao Dong; Meirong Li; Changlin Deng; Guodong Wang; Yongjie Liu (Veterinary Microbiology, 2026)

Enzymatically extracted rose bee pollen significantly alleviates BPH and hyperlipidemia-aggravated progression by targeting COX-2 inhibition - Yishu Sun; Fangci Xiong; Zitian Chen; Zhisheng Wang; Xinyang Lu; Xiangchun Meng; Yaning Chang; Yingjun Zhou (Food Bioscience, 2025)

Adaptive filtering AHU: A novel approach for balancing the efficient filtering performance and energy conservation - Shibo Wang; Bo Xiang; Chaoyan Sun; Pengfei Si; Lijun Shi; Jikang Jia; Yingjun Guo; Ping Guo (Building and Environment, 2025)

Integrated transcriptome and BSA-seq analysis identifies a novel QTL for Meloidogyne graminicola resistance in rice HuaHang31 - Zhuhong Yang; Qingyan Xiao; Yao Wang; Yingjun Zhang; Shan Ye; Pingyong Sun; Wuhan Zhang; Huafeng Deng; Shiming Liu; Zhong Ding (Theoretical and Applied Genetics, 2025)

Temporal and spatial pattern, sources, and main controlling factors of odor compounds in Qiandaohu Reservoir - Yi Chi; Zhanpu Tang; Yingjun Zhu; Lingjia Wang; Tianli Chen; Ping He; Yuxin Chen; Tong Sun; Siying Cai; Weijun zhang (Environmental Monitoring and Assessment, 2025)
The ubiquitous presence of algal-derived odors in large lakes and reservoirs constitutes a critical environmental concern. Particularly during the high-temperature summer months, localized regions of Qiandaohu Reservoir have exhibited markedly elevated concentrations of odor compounds. To investigate the intricate relationships among odor compounds, algae communities, and environmental factors in Qiandaohu Reservoir, and to forestall the impact of odor compounds on the quality of drinking water, this research implemented a systematic monthly survey to monitor several types of odor compounds, algal communities, physicochemical factors, and associated synthetases. The result demonstrated that the odor issue in Qiandaohu Reservoir is not yet severe. Among the detected compounds, dimethyl sulfide, dimethyldisulfide, and β-cyclocitral were all below the odor threshold, while dimethyl trisulfide, 2-methylisoborneol, geosmin, and β-ionone exceeded the odor threshold in some samples. The odor compounds are jointly influenced by abiotic environmental conditions and algae, presenting conspicuous horizontal, vertical, and seasonal distribution disparities. Notably, total nitrogen, total phosphorus, and the TN/TP ratio exert a substantial influence. Algae play a pivotal role in contributing to these odor compounds, warranting particular attention to the composition and dynamic alterations of the algal community during the summer and autumn seasons. This research comprehensively investigates the spatiotemporal patterns, sources, and controlling factors of odor compounds in a large drinking water source reservoir with relatively lower trophic status, providing new insights into odor management in such ecosystems.

Investigate the Effect of ZFP64 on mRNA Expression of HBG Based on Bioinformatics and Experimental Validation - Siqi Huang; Jianfeng Wu; Yinghong Yang; Mingming Zhu; Lihao Chen; Shunhan Zhang; Yi Yang; Xiaofang Sun; Yingjun Xie (Cell Biochemistry and Biophysics, 2025)

Degradation of bisphenol F by peroxymonosulfate activated with palladium-based catalysts - Xiaomei Zhou; Minghui Li; Jifei Hou; Jingya Sun; Shourong Zheng; Yingjun Chen; Qingxin Guan (Journal of Environmental Sciences, 2025)

Exploring the spatial heterogeneity of soil organic carbon and the influence of coastal factors: A case study in the Yellow River Delta, China - Youxiao Wang; Yingjun Sun; Qi Wang; Pingjie Fu; Yaohui Liu; Fang Wang; Fei Meng (Science of The Total Environment, 2025)

Enhancing butyrate synthesis and intestinal epithelial energy supply through mixed probiotic intervention in dextran sulfate sodium-induced colitis - Heng Zhang; Jingzhou Sun; Aowen Xie; Huiqin Yang; Yingjun Li; Yuxia Mei; Jinshan Li; Lei Xiao; Yangyang Liu; Yunxiang Liang (Food Bioscience, 2025)

The reduction of the carbon footprint of municipal solid waste management via source classification and supporting strategies: An analysis for the megacity of Shenzhen - Lei Zhang; Huan Li; Tao Hu; Xinrui Du; Yingjun Zhou; Guofen Sun; Jianguo Liu (Waste Management, 2024)

The spatio-temporal evolution of spatial structure and supply-demand relationships of the ecological network in the Yellow River Delta region of China - Zhe Zhang; Qi Wang; Yougui Feng; Yingjun Sun; Na Liu; Sijia Yan (Journal of Cleaner Production, 2024)

Study on the synthesis of branched coagulants and the mechanism of strengthening oil–water separation - Hailin Yu; Huili Zhang; Meijuan Hu; Gang Liu; Zhengnan Sun; Jingxue Xu; Yingjun Wang; Guolin Jing; Hongsheng Liu (Fuel, 2024)

Assessing spatiotemporal risks of nonpoint source pollution via soil erosion: a coastal case in the Yellow River Delta, China - Youxiao Wang; Chong Huang; Gaohuan Liu; Zhonghe Zhao; He Li; Yingjun Sun (Environmental Science and Pollution Research, 2024)

Preparation of microencapsulated coagulants and application to oil–water separation under gravity coagulation conditions - Hailin Yu; Huili Zhang; Gang Liu; Xin Chen; Xuyu Chen; Yihai Yang; Zhengnan Sun; Long Tang; Long Dong; Yingjun Wang; Hongsheng Liu (Fuel, 2024)

Preparation and characteristic study of the hydrogel of coal spontaneous combustion environmental protection - Yansong Zhang; Yingjun Sun; Wenzhou Du; Hongtao Dong; Bowen Wang; YangXu Wang; Xingxing Cao (Fuel, 2024)

Saracatinib prompts hemin-induced K562 erythroid differentiation but suppresses erythropoiesis of hematopoietic stem cells - Lina Ding; Diyu Chen; Yuanshuai Li; Yingjun Xie; Xiaofang Sun; Ding Wang (Human Cell, 2024)
Human myeloid leukemia cells (such as K562) could be used for the study of erythropoiesis, and mature erythroid markers and globins could be induced during leukemia cell differentiation; however, the pathways involved are different compared with those of hematopoietic stem cells (HSCs). We identified the differentially expressed genes (DEGs) of K562 cells and HSCs associated with stem cells and erythroid differentiation. Furthermore, we showed that hemin-induced differentiation of K562 cells could be induced by serum starvation or treatment with the tyrosine kinase inhibitor saracatinib. However, erythroid differentiation of HSCs was inhibited by the deprivation of the important serum component erythropoietin (EPO) or treatment with saracatinib. Finally, we found that the mRNA expression of K562 cells and HSCs was different during saracatinib-treated erythroid differentiation, and the DEGs of K562 cells and HSCs associated with tyrosine-protein kinase were identified. These findings elucidated the cellular phenomenon of saracatinib induction during erythroid differentiation of K562 cells and HSCs, and the potential mechanism is the different mRNA expression profile of tyrosine-protein kinase in K562 cells and HSCs.

Retrieval of high-precision precipitable water vapour maps using Sentinel-1A and Beidou satellite data - Qiuying Guo; Miao Yu; Dewei Li; Shoukai Huang; Xuelong Xue; Yingjun Sun (International Journal of Remote Sensing, 2023)

Grazing facilitates litter-derived soil organic carbon formation in grasslands by fostering microbial involvement through microenvironment modification - Yuqi Wei; Bin Wei; Masahiro Ryo; Yixian Bi; Xiangyun Sun; Yingjun Zhang; Nan Liu (CATENA, 2023)

Genetic dissection of grain morphology and yield components in a wheat line with defective grain filling - Bingyan Liu; Lingli Li; Chao Fu; Yingjun Zhang; Bin Bai; Jiuyuan Du; Jianqi Zeng; Yingjie Bian; Siyang Liu; Jie Song; Xumei Luo; Lina Xie; et al. (Theoretical and Applied Genetics, 2023)

Forms of nitrogen inputs regulate the intensity of soil acidification - Ze Wang; Tingting Tao; Hu Wang; Ji Chen; Gaston E. Small; David Johnson; Jihui Chen; Yingjun Zhang; Qichao Zhu; Shengmin Zhang; Yantao Song; Jens Kattge; et al. (Global Change Biology, 2023)
Soil acidification induced by reactive nitrogen (N) inputs can alter the structure and function of terrestrial ecosystems. Because different N‐transformation processes contribute to the production and consumption of H + , the magnitude of acidification likely depends on the relative amounts of organic N (ON) and inorganic N (IN) inputs. However, few studies have explicitly measured the effects of N composition on soil acidification. In this study, we first conducted a meta‐analysis to test the effects of ON or IN inputs on soil acidification across 53 studies in grasslands. We then compared soil acidification across five different ON:IN ratios and two input rates based on long‐term field N addition experiments. The meta‐analysis showed that ON had weaker effects on soil acidification than IN when the N addition rate was above 20 g N m −2 year −1 . The field experiment confirmed the findings from meta‐analysis: N addition with proportions of ON ≥ 20% caused less soil acidification, especially at a high input rate (30 g N m −2 year −1 ). Structural equation model analysis showed that this result was largely due to a relatively low rate of H + production from ON as NH 3 volatilization and uptake of ON and NH 4 + by the dominant grass species Leymus chinensis (which are both lower net contributors to H + production) result in less NH 4 + available for nitrification (which is a higher net contributor to H + production). These results indicate that the evaluation of soil acidification induced by N inputs should consider N forms and manipulations of relative composition of N inputs may provide an effective approach to alleviate the N‐induced soil acidification.

Ultrafast high-temperature sintering of polymer-derived ceramic nanocomposites for high-temperature thin-film sensors - Chao Wu; Yanzhang Fu; Yingjun Zeng; Guochun Chen; Xiaochuan Pan; Fan Lin; Lida Xu; Qinnan Chen; Daoheng Sun; Zhenyin Hai (Chemical Engineering Journal, 2023)

Optimization on building combined cooling, heating, and power system considering load uncertainty based on scenario generation method and two-stage stochastic programming - Yingjun Ruan; Fanyue Qian; Ke Sun; Hua Meng (Sustainable Cities and Society, 2023)

Precipitation-Dissolution switchable surfactants with the potential of simultaneous retrieving of surfactants and hydrophobic organic contaminants from emulsified and micellar eluents - Jiajie Pan; Lianlian Sun; Xuefeng Liu; Yingjun Fang (Chemical Engineering Journal, 2023)

Temperature-insensitive conductive composites for noninterference strain sensing - Chao Wu; Fan Lin; Xiaochuan Pan; Yingjun Zeng; Guochun Chen; Lida Xu; Yingping He; Gonghan He; Qinnan Chen; Daoheng Sun; Zhenyin Hai (Chemical Engineering Journal, 2023)

Construction of Greenspace Landscape Ecological Network Based on Resistance Analysis of GeoDetector in Jinan - Han Guo; Yingjun Sun; Qi Wang; Xvlu Wang; Liguo Zhang (Stochastic Environmental Research and Risk Assessment, 2023)

Altered topological properties of the intrinsic functional brain network in patients with right-sided unilateral hearing loss caused by acoustic neuroma - Zhiyuan Fan; Zhen Fan; Tianming Qiu; Liuxun Hu; Yuan Shi; Yunman Xia; Xiaoyi Sun; Yingjun Liu; Sichen Li; Mingrui Xia; Wei Zhu (Brain Imaging and Behavior, 2022)

Spatio-temporal baseline and spatial coverage of lunar-based SAR repeat-track interferometry in single- and double-antenna configurations - Jinglong Dong; Qiang Shen; Houjun Jiang; Liming Jiang; Dewei Li; Hansheng Wang; Xiaodong Chen; Yingjun Sun; Guobiao Yao (International Journal of Remote Sensing, 2022)

Association of urinary phthalate metabolites with sarcopenia in US adults: NHANES 1999–2006 - Ye Yang; Li Ju; Jiayao Fan; Shaofang Cai; Lingling Sun; Yingjun Li (Environmental Science and Pollution Research, 2022)

Mycorrhizal and rhizobial interactions influence model grassland plant community structure and productivity - Jiqiong Zhou; Gail W. T. Wilson; Adam B. Cobb; Yingjun Zhang; Lin Liu; Xinquan Zhang; Feida Sun (Mycorrhiza, 2022)

Comparison and analysis of SWDs retrieval from GPS/BDS and validation with ray-traced delays - Qiuying Guo; Xuxiang Wu; Yingjun Sun; Wengang Sang; Dewei Li (Meteorology and Atmospheric Physics, 2021)

Spatial variation and influence factor analysis of soil heavy metal As based on geoDetector - Xvlu Wang; Yingjun Sun; Liping Zhang; Yuang Mei (Stochastic Environmental Research and Risk Assessment, 2021)

Genome-Wide Investigation of Major Enzyme-Encoding Genes in the Flavonoid Metabolic Pathway in Tartary Buckwheat (Fagopyrum tataricum) - Yingjun Yao; Lei Sun; WenJing Wu; Shuang Wang; Xin Xiao; MinLun Hu; ChengLei Li; HaiXia Zhao; Hui Chen; Qi Wu (Journal of Molecular Evolution, 2021)

Correction to: Evolutionary and recombination analysis of porcine reproductive and respiratory syndrome isolates in China - Zhendong Zhang; Xiangyang Qu; Hongliang Zhang; Xudong Tang; Ting Bian; Yingjun Sun; Mingming Zhou; Fubo Ren; Ping Wu (Virus Genes, 2020)

Influence factor analysis of soil heavy metal Cd based on the GeoDetector - Yunting Jiang; Yingjun Sun; Liping Zhang; Xvlu Wang (Stochastic Environmental Research and Risk Assessment, 2020)

Evolutionary and recombination analysis of porcine reproductive and respiratory syndrome isolates in China - Zhendong Zhang; Xiangyang Qu; Hongliang Zhang; Xudong Tang; Ting Bian; Yingjun Sun; Mingming Zhou; Fubo Ren; Ping Wu (Virus Genes, 2020)

Plant functional group influences arbuscular mycorrhizal fungal abundance and hyphal contribution to soil CO2 efflux in temperate grasslands - Weiyang Gui; Haiyan Ren; Nan Liu; Yingjun Zhang; Adam B. Cobb; Gail W. T. Wilson; Xiao Sun; Jian Hu; Yan Xiao; Fengge Zhang; Gaowen Yang (Plant and Soil, 2018)

Trichoderma improves the growth of Leymus chinensis - Fengge Zhang; Yunqian Huo; Xixi Xu; Jian Hu; Xiao Sun; Yan Xiao; Yingjun Zhang (Biology and Fertility of Soils, 2018)

Increased precipitation modulates the influence of nitrogen and litter inputs on the nutrient resorption proficiency rather than efficiency of Leymus chinensis - Yue Shen; Xin Yang; Xiao Sun; Wenqing Chen; Gaowen Yang; Nan Liu; Jishan Chen; Yingjun Zhang (Plant Ecology, 2018)

Rapid detection of highly pathogenic porcine reproductive and respiratory syndrome virus by a fluorescent probe-based isothermal recombinase polymerase amplification assay - Yang Yang; Xiaodong Qin; Yingjun Sun; Ting Chen; Zhidong Zhang (Virus Genes, 2016)

Effects of heterogeneous salinity on growth, water uptake, and tissue ion concentrations of alfalfa - Juanjuan Sun; Gaowen Yang; Wenjun Zhang; Yingjun Zhang (Plant and Soil, 2016)

Identification of a linear B-cell epitope on the avian leukosis virus P27 protein using monoclonal antibodies - Xiaofei Li; Liting Qin; Haibo Zhu; Yingjun Sun; Xuezhi Cui; Yadong Gao; Xiaole Qi; Yongqiang Wang; Honglei Gao; Yulong Gao; Xiaomei Wang (Archives of Virology, 2016)

Effect of Change of Mechanical Ventilation Position on the Treatment of Neonatal Respiratory Failure - Jiebin Wu; Jingfang Zhai; Hongxia Jiang; Yingjun Sun; Bao Jin; Yanyan Zhang; Bin Zhou (Cell Biochemistry and Biophysics, 2015)

Thyroid hormone responsive protein spot 14 enhances lipogenesis in bovine mammary epithelial cells - Yingjun Cui; Zhiyu Liu; Xia Sun; Xiaoming Hou; Bo Qu; Feng Zhao; Xuejun Gao; Zhe Sun; Qingzhang Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Modeled Dosage–Response Relationship on the Net Photosynthetic Rate for the Sensitivity to Acid Rain of 21 Plant Species - Shihuai Deng; Shuzhen Gou; Baiye Sun; Wenlin Lv; Yuanwei Li; Hong Peng; Hong Xiao; Gang Yang; Yingjun Wang (Bulletin of Environmental Contamination and Toxicology, 2012)